(untitled) - Can Tho University (Can Tho ( Viet Nam ), 2000)
The objective of the workshop is to exchange experience and research outcomes among researchers in VNRP and outside and to introduce the research results in rice-fish farming to the beneficiaries in the whole country: agricultural and rural development policy makers and managers, agriculture and fishery extension workers at the national and local agencies,...
Keywords: Fisheries